Molecular and Cellular Characterization of Human CD8 T Suppressor Cells - Xu, Zheng; Ho, Sophey; Chang, Chih-Chao; Zhang, Qing-Yin; Vasilescu, Elena-Rodica; Vlad, George; Suciu-Foca, Nicole (Frontiers in Immunology, 2016)
Bidirectional interactions between dendritic cells (DC) and Ag-experienced T cells initiate either a tolerogenic or immunogenic pathway. The outcome of these interactions is of crucial importance in malignancy, transplantation, and autoimmune diseases. Blockade of co-stimulation results in the induction of T helper cell anergy and subsequent differentiation of antigen specific CD8+ T suppressor/regulatory cells (Ts). Ts. Primed in the presence of inhibitory signals exert their inhibitory function in an antigen specific manner, a feature with tremendous clinical potential. In transplantation or autoimmunity, antigen specific Ts can enforce tolerance to auto- or alloantigens, while otherwise leaving the immune response to pathogens uninhibited. Alternatively, blockade of inhibitory receptors results in the generation of cytolytic CD8+ T cells (CTL), which is vital towards defense against tumors and viral diseases. Because CD8 T cells are MHC Class I restricted, they are able to recognize HLA-bound antigenic peptides presented not only by APC, but also on parenchymal cells, thus eliciting or suppressing auto- or allo- immune reactions.